Adherence and electrochemical behavior of calcium titanate coatings onto 304 stainless steel substrate (2014)
Calcium titanate has been proposed as a coating for biomedical applications but it has not been reported characterization of adhesion failure mechanisms or electrochemical properties in time. In this work have been studied these properties of a calcium titanate coating growth onto AISI 304 steel deposited by r.f. magnetron sputtering. It was found that the coating has a critical adhesive load of 6.53 § 0.14 N.With respect to its electrochemical properties potentiodynamic polarization curves show that the calcium titanate coating provides protection to AISI 304 steel. However, EIS indicates that even though metal dissolution occur through the pores in the coating, this leads to the precipitation of salts that block pores; this precipitates layer acts like an additional barrier to the metal dissolution in the system